2015
DOI: 10.1111/jgh.12979
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities of gastrointestinal mucosa in celiac disease: An in vitro proton nuclear magnetic resonance spectroscopy study

Abstract: NMR spectroscopy with multivariate analysis of duodenal mucosal biopsies revealed a characteristic metabolic profile in CeD patients. The work provided an insight in determining biomarker/s for villous atrophy and diagnosis of CeD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Also the results suggested that elevated level of aspartate in intestinal mucosa may lead to deficiency of aspartate for urea cycle in liver and thus may contribute to liver abnormalities associated with CeD. Furthermore, the significantly higher concentrations of pyruvate and succinate in intestinal mucosa of patients with CeD in comparison to controls suggests abnormality in glycolysis metabolic pathway and Kreb's cycle, thus leading to energy deficiency in CeD [38].…”
Section: Intestinal Mucosamentioning
confidence: 88%
See 4 more Smart Citations
“…Also the results suggested that elevated level of aspartate in intestinal mucosa may lead to deficiency of aspartate for urea cycle in liver and thus may contribute to liver abnormalities associated with CeD. Furthermore, the significantly higher concentrations of pyruvate and succinate in intestinal mucosa of patients with CeD in comparison to controls suggests abnormality in glycolysis metabolic pathway and Kreb's cycle, thus leading to energy deficiency in CeD [38].…”
Section: Intestinal Mucosamentioning
confidence: 88%
“…Recently, NMR based metabonomics approach using samples like urine, blood plasma/sera and mucosa samples showed putative biomarkers for the diagnosis of CeD [4,16,38]. These studies demonstrated that in-vitro high-resolution NMR spectroscopy may emerge as a promising tool for the evaluation of CeD through the analysis of intestinal mucosal biopsies, body fluids and faecal extracts.…”
Section: Upadhyay Et Al / Review: Role Of Nmr Metabonomics In Celmentioning
confidence: 99%
See 3 more Smart Citations